2009
DOI: 10.1002/bit.22505
|View full text |Cite
|
Sign up to set email alerts
|

Substrate uptake, phosphorus repression, and effect of seed culture on glycopeptide antibiotic production: Process model development and experimental validation

Abstract: Actinomycetes, the soil borne bacteria which exhibit filamentous growth, are known for their ability to produce a variety of secondary metabolites including antibiotics. Industrial scale production of such antibiotics is typically carried out in a multi-substrate medium where the product formation may experience catabolite repression by one or more of the substrates. Availability of reliable process models is a key bottleneck in optimization of such processes. Here we present a structured kinetic model to desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…In our previous work, it was shown that balhimycin production was signiWcantly inXuenced by phosphate concentration in deWned media [14]. SpeciWcally, increasing phosphate concentration beyond the optimal value led to higher biomass growth but lower balhimycin production.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…In our previous work, it was shown that balhimycin production was signiWcantly inXuenced by phosphate concentration in deWned media [14]. SpeciWcally, increasing phosphate concentration beyond the optimal value led to higher biomass growth but lower balhimycin production.…”
Section: Resultsmentioning
confidence: 97%
“…Our previous work has shown that the concentration of ammonia has a signiWcant eVect on balhimycin productivity [14]. Therefore, we wanted to investigate whether variation in ammonia aVected morphology.…”
Section: Evect Of Ammonium Sulfate In Dewned Mediummentioning
confidence: 99%
See 2 more Smart Citations
“…Further, inhibition of glucose was also taken into account. Therefore, the Monod model was modified to account for the inhibitions of substrates and product by incorporating two additional parameters, n and S max , for each substrate and product as proposed by Luong [18] and Maiti et al [19], respectively. The Leudeking-Piret model was used to investigate the product formation for both the wild and mutant strains of S. roseosporus.…”
Section: Model Developmentmentioning
confidence: 99%